The Influence of Intellectual Intelligence, Emotional Intelligence and Spiritual Intelligence on Understanding Magnitude of Behavioral Accounting - Widhianningrum, Purweni (Universitas Negeri Malang, 2017)
This study aimed to examine the effect of intellectual, emotional and spiritual quotient to the level of understanding behavioral accounting. This population are Accounting Education students who are taking a behavioral accounting class, amounted to 87 students. Purposive sampling was done to sampling technique, so the total sample used are 81 respondents. Data analysis method used is multiple regression. The results showed that among the intellectual, emotional, and spiritual quotient which is owned accounting student, there only intellect quotient that is positive and significant impact on the level of understanding of behavioral accounting. This indicates that the level of understanding of behavioral accounting at the undergraduate program is still on the cognitive aspects. Thus, accounting behavioral simply understood as a method should be implemented and applied when they were faced with a condition that requires make a logical reasoning of all the problems in the field of accounting.Â Keywords: intellectual quotient, emotional quotient and spiritual quotient, and behavioral accounting